Investigation of using strain gauge in tension, torsion and bending experiments - Kaner, Billur; Asmaz, Kerem (YILDIZ TECHNICAL UNIV, 2024)
In the engineering approach, the calculation of stress-strain values is crucial for determining the mechanical properties of materials. It is known that stress values could be calculated using the cross-section area, the moment of inertia of the material, and even strain values. However, the experimental determination of strain values is somewhat more complicated. In strain calculation, a video- extensometer and strain gauge are generally utilized. The goal of this study is to determine the strain values of the steel material in the linear region with experimental, theoretical and numerical approaches and to examine the suitability of the use of strain gauges for bending, torsion and tensile tests. Three sets (Tension, Torsion and Bending) were prepared in the experimental approach, and strain values were obtained for each experimental set-up. Furthermore, geometric models similar to experimental design were applied to ANSYS finite element program in numerical analyses. Additionally, the strain values were determined theoretically using the full bridge approach in Wheatstone Bridge Theorem. It is thought that assessing the use of the Wheatstone bridge, examining, and comparing the theoretical approaches of different loadings, modelling the appropriate experimental methods in the finite element program, and getting results, and finally interpreting these results, make a valuable contribution to the literature. The strain values were compared. Accordingly, the mean error values between theoretical and numerical for tensile, bending and torsion tests are 5.17%, 4.23% and 6.26%, respectively. The mean error values between the theoretical-experimental results of the same tests were 7.08%, 3.48% and 4.89%, respectively. Consequently, it was seen that experimental, numerical, and theoretical approaches gave more convergence points for each test.
Keywords: Bending; Finite Element Analysis; Strain gauge; Tension; Torsion; WHEATSTONE BRIDGE; CONCRETE; TESTS; Engineering